Case History -A Painful Toe - IB Mcintosh (Global Journal of Medical and Clinical Case Reports - Peertechz Publications, 2019)
A 21 year old man was complaining of pain in a toe with swelling, which was interfering with his walking. The lesion was itchy and nodular. He thought he had been bitten and the insect had left a bump and black mark on the skin. Over a few days, the lesion had shrunk in size, turned brown, and wrinkled. He had recently returned from a Caribbean holiday and had been swimming and walking bare foot on the sands. He had been bitten by a sand fl y. Tunga penetrans (chigoe fl ea or jigger) is a parasitic insect found in most tropical and sub-tropical climates. It is native to Central and South America, and has been introduced by humans to sub-Saharan Africa. In its parasitic phase it has signifi cant impact on its host. A parasitical infestation of T. penetrans is called tungiasis.